FORECASTING THE COMPETITIVENESS OF AN ENTERPRISE (Conferencea, 2023)
The competitiveness of the industrial sector is based on the formation of related factors: the production sector of an industrial enterprise, human resources, financial and material resources, etc. The assessment of the competitiveness of industrial enterprises is based on a methodology that comprehensively takes into account the various activities of the industrial enterprise under study based on a comparative analysis with leading competitors in the context of two main areas: current competitiveness and competitive potential of the production complex. Of particular importance is the competitive intelligence toolkit, which helps to find the necessary approach in a difficult situation for the enterprise. In this paper, the author provides a theoretical analysis of the research of foreign and domestic authors of methodological tools for forecasting the competitiveness of enterprises, studied a large number of scientific articles and studies on this topic.The purpose of this work is the theoretical and practical substantiation of methodological tools for forecasting the competitiveness of an enterprise based on the Elliott wave principle, as well as developing a model for assessing the forecast of competitiveness of enterprises based on the Elliott wave principle and using the Fibonacci spiral.